Porous composite material based on MOFs (Metal-Organic Frameworks) material as well as preparation method and application thereof
By using a combination technology of polyhydroxy polymer binder and curing agent, the problems of low load, unevenness and insufficient adhesion in MOFs material coating technology are solved, and a MOF adhesion layer with high adhesion rate and mechanical strength is achieved, extending the service life of the material.
Patent Information
- Application Number
- CN202510616500.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-14
- Publication Date
- 2025-06-13
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing MOFs material coating technology has problems such as low load, uneven coating, insufficient adhesion, resulting in reduced material performance and short service life.
The combination of polyhydroxy polymer adhesive and curing agent is used, and the MOF slurry is distributed on the surface of the base material by immersion or spraying, and then the secondary curing process is carried out to improve the mechanical strength and adhesion of the MOF adhesion layer.
It significantly improves the adhesion rate and mechanical strength of MOFs materials, prevents the adhesion layer from falling off, extends the service life of the material, and improves its operating efficiency.
Smart Images

Figure CN120132798A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of MOFs material coating, and particularly relates to a porous composite material based on MOFs material, a preparation method thereof, and an application thereof. Background Art
[0002] As a new type of porous material, MOFs materials (metal-organic framework materials) show great application prospects in various adsorption scenarios. However, similar to traditional molecular sieve materials, the synthesized MOFs materials are powders macroscopically, and they need to be formed into shapes for practical production and life applications. The most common method is to coat the powder material on a substrate material to form a porous composite material. Although traditional molecular sieves have relatively mature coating processes, the coating process of molecular sieves cannot be directly applied to MOFs materials because of their huge differences in physical and chemical properties.
[0003] In practical applications, MOFs materials need to be combined with substrate materials to form device products or materials, such as porous composite materials. Problems such as material stability and reduction of material performance may be involved in this process. Therefore, a coating process suitable for the characteristics of MOFs needs to be developed. There are still many problems in the current MOFs material coating process. For example, the loading amount during the coating process is low, which means that the thickness and coverage of the coating are limited, affecting its performance. During the coating process, if the slurry distribution is uneven, it may lead to inconsistent coating thickness, affecting the adsorption performance and mechanical stability of the material. And the adhesion between the coating material and the MOFs material is insufficient, which will also cause the coating to fall off during use, reducing the service life and efficiency of the material. For example, there are reports on the processes of hot pressing and spraying. Among them, the MOF yield obtained by the hot pressing method is low, resulting in low adsorption capacity and short cycle period, etc.; the spraying method is prone to the phenomenon of runner powder falling (MOF powder falling off) due to the lack of adhesion or binding force between the MOF and the substrate. There is also a patent proposing to mix MOF powder with a bonding aid to form a coating slurry and then coat it on a honeycomb carrier. However, this scheme requires a large amount of organic solvents to prepare the slurry, which is not only costly but also environmentally unfriendly. There is also a MOF slurry coating scheme proposed in the literature that only uses water as a solvent, solving the problems of high cost and environmental unfriendliness; however, this technology is only applicable to the coating of Fe-MOF on a glass fiber substrate, with a single applicable system and a large amount of binder used; more importantly, it also requires high-temperature curing treatment at 300 degrees Celsius after coating, with a cumbersome process and high energy consumption.
[0004] Therefore, in the coating technology of MOFs materials, achieving high loading, coating uniformity, and high coating adhesion are the main technical challenges. Developing a reasonable coating scheme is crucial for the practical application of MOFs materials. This not only involves increasing the loading of MOFs and the uniformity of the coating but also enhancing the durability and stability of the coating to meet the requirements of the actual working environment. Summary of the Invention
[0005] The present invention aims to solve at least one of the technical problems existing in the above-mentioned prior art. For this purpose, the present invention provides a porous composite material based on MOFs materials, a preparation method thereof, and an application thereof. The preparation method provided by the present invention can not only significantly improve the adhesion rate of MOFs materials but also remarkably enhance the mechanical strength of the MOF adhesion layer, effectively prevent the detachment of the adhesion layer caused by insufficient adhesion between the adhesion layer and the substrate material, and enhance the durability and stability of the adhesion layer.
[0006] The present invention provides a preparation method of a porous composite material based on MOFs materials.
[0007] Specifically, a preparation method of a porous composite material based on MOFs materials includes the following steps: Disperse the MOFs materials to obtain a MOF slurry; then add a polyhydroxy polymer binder to obtain a mixed slurry; distribute the mixed slurry on the surface of the substrate material by impregnation or spraying, and obtain a primary porous composite material after drying and curing; then impregnate the primary porous composite material with a curing agent, and finally obtain a porous composite material based on MOFs materials after drying; The curing agent is selected from at least one of calcium chloride, calcium sulfate, zinc chloride, magnesium chloride, zinc nitrate, and barium chloride; the polyhydroxy polymer binder is selected from at least one of sodium alginate, chitosan, and hyaluronic acid; The addition amount of the polyhydroxy polymer binder is 1.0% - 12.0% of the mass of the MOFs materials.
[0008] In some embodiments of the present invention, the curing agent is selected from at least one of calcium chloride, calcium sulfate, zinc chloride, zinc nitrate, and barium chloride.
[0009] In some embodiments of the present invention, the MOFs materials include at least one of MOF-801 series, MOF-808 series, MIL series, UiO-66 series, ZIF series, and PCN series MOFs materials.
[0010] In some embodiments of the present invention, the concentration of the MOF slurry is 0.1 g / mL - 1.0 g / mL.
[0011] In some embodiments of the present invention, the addition amount of the polyhydroxy polymer binder is 1.2% - 10.0% of the mass of the MOFs material. Preferably, the addition amount of the polyhydroxy polymer binder is 1.5% - 8.0% of the mass of the MOFs material.
[0012] In some embodiments of the present invention, the substrate material includes one of glass fiber paper, non-woven fabric, metal products, sponge, and silicone products. Among them, glass fiber includes glass fiber paper, honeycomb glass fiber wheel disc, etc.
[0013] In some embodiments of the present invention, after the curing agent is formulated into a curing agent solution, the primary porous composite material is impregnated therewith, and the concentration of the curing agent solution is 0.05 g / mL - 1.0 g / mL; preferably, the concentration of the curing agent solution is 0.1 g / mL - 0.5 g / mL.
[0014] The present invention also provides a porous composite material based on MOFs material.
[0015] Specifically, a porous composite material based on MOFs material is prepared by the above preparation method; the porous composite material includes a substrate material and MOFs material attached to the surface of the substrate material.
[0016] In some embodiments of the present invention, the attachment rate of the MOFs material is greater than 30%.
[0017] The present invention also provides an application of the above porous composite material based on MOFs material.
[0018] Specifically, the application of the above porous composite material based on MOFs material in the preparation of porous adsorption materials.
[0019] Compared with the prior art, the beneficial effects of the present invention are as follows: (1) In the present invention, the MOFs material is first mixed with the polyhydroxy polymer binder, impregnated or sprayed on the surface of the substrate material to obtain a primary porous composite material with an attachment layer, and then it is impregnated with a curing agent to obtain a porous composite material based on MOFs material. By the combined use of the polyhydroxy polymer binder and the curing agent, as well as the selection of the curing agent and the binder, and utilizing the chelation effect between the polyhydroxy groups in the specific binder and the metal ions of the curing agent, the secondary curing and strengthening of the MOF coating are realized, which can not only greatly improve the attachment rate of the MOFs material; but also significantly improve the mechanical strength of the MOF attachment layer, effectively prevent the detachment of the attachment layer caused by insufficient adhesion between the attachment layer and the substrate material, thereby significantly extending the service life of the material and improving its operation efficiency.
[0020] (2) The porous composite material based on MOFs material prepared by the present invention enhances the adhesion force and adsorption of the adhesion layer by utilizing the acting force provided by vacant metal sites or ligands in the pores of the MOFs material. The adhesion rate of the adhesion layer of the prepared porous composite material is as high as 45% (mass fraction with respect to the substrate material), and the powder loss rate within 24 hours is less than 0.5%, as low as 0.1%.
[0021] (3) The preparation method provided by the present invention can maintain the structural stability of the MOFs material and will not cause the collapse of the framework structure of the MOFs material; this preparation method will not change the pore environment of the adhesion layer of the MOFs material, and can maintain the characteristics of high specific surface area and excellent adsorption performance of the MOFs material.
[0022] (4) The method provided by the present invention can coat and combine the MOFs material with a variety of different substrate materials to form a variety of porous composite materials based on the MOFs material, which has a wide adaptation range and can meet the growing application requirements of the MOFs material. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 X-ray diffraction pattern of the porous composite material prepared by using UiO-66 series MOFs material in Example 1; Figure 2 X-ray diffraction pattern of the porous composite material prepared by using MIL-101 series MOFs material in Example 2; Figure 3 X-ray diffraction pattern of the porous composite material prepared by using MOF-801 series MOFs material in Example 3; Figure 4 X-ray diffraction pattern of the porous composite material prepared by using MIL-100 series MOFs material in Example 4; Figure 5 X-ray diffraction pattern of the porous composite material prepared by using MOF-808 series MOFs material in Example 5; Figure 6 X-ray diffraction pattern of the porous composite material prepared by using MIL-160 series MOFs material in Example 6; Figure 7 Nitrogen adsorption and desorption isotherm of the porous composite material prepared by using UiO-66 series MOFs material in Example 1; Figure 8 Nitrogen adsorption and desorption isotherm of the porous composite material prepared by using MIL-101 series MOFs material in Example 2; Figure 9 Nitrogen adsorption and desorption isotherm of the porous composite material prepared by using MOF-801 series MOFs material in Example 3; Figure 10 This is the nitrogen adsorption-desorption curve of the porous composite material prepared using the MIL-100 series MOFs material in Example 4; Figure 11 This is the nitrogen adsorption-desorption curve of the porous composite material prepared using MOF-808 series MOFs material in Example 5; Figure 12 This is the nitrogen adsorption-desorption curve of the porous composite material prepared using the MIL-160 series MOFs material in Example 6. DETAILED DESCRIPTION
[0024] In order to make the technical scheme of the present invention more clearly understood by those skilled in the art, the following embodiments are listed for illustration. It should be pointed out that the following embodiments do not limit the protection scope of the present invention.
[0025] Unless otherwise specified, the raw materials, reagents or devices used in the following experimental examples and embodiments can be obtained from conventional commercial sources or by existing known methods.
[0026] Experimental Example 1 The effects of adding different binders and not adding binders on the properties of porous composite materials based on MOFs materials are studied. The specific operations are as follows: A certain amount of UiO-66 MOFs material was weighed and evenly dispersed in water to form a uniform suspension with a concentration of 0.5 g / mL. Subsequently, different binders (sodium alginate, chitosan, starch, hyaluronic acid, polyvinyl alcohol, sodium cellulose) and no binder were added to the suspension, and the mass of the binder accounted for 5% of the mass of the MOFs material, and a uniform slurry was formed by sufficient stirring.
[0027] Completely immerse the glass fiber paper disc in the MOF slurry, hold for 1 minute, pull out, immerse again, and repeat 3 times to ensure that the fiber is fully impregnated. Then use a blower to remove excess slurry on the fiber surface to prevent the coating from being too thick or uneven. Subsequently, the treated glass fiber paper is placed in a 120°C oven for heat drying to promote the volatilization of the solvent in the slurry and the curing of the material. After drying, take out the glass fiber paper and let it cool naturally to room temperature. Then immerse the glass fiber paper in a 0.1g / mL curing agent calcium chloride solution for 10 minutes. Finally, the treated glass fiber paper is placed in a 120°C oven for heat drying to obtain a composite material.
[0028] Performance test: The coating rate (adhesion rate) of MOFs materials was measured by weighing and comparing; the prepared porous composite material was weighed after being blown by wind at 50 m / s for 24 hours, and the adhesion layer shedding rate (24-hour powder loss rate) was calculated by the mass of the porous composite material before and after blowing. The test results are shown in Table 1.
[0029] Table 1
[0030] Experimental Example 2 The effect of binder dosage on the properties of porous composite materials based on MOFs materials was studied. The specific operation is as follows: A certain amount of UiO-66 MOFs material was weighed and evenly dispersed in water to form a uniform suspension with a concentration of 0.5 g / mL. Subsequently, different amounts of binder sodium alginate (the mass of the binder accounted for 0.5%, 1%, 1.5%, 2%, 5%, 6%, and 8% of the mass of the MOFs material) were added to the suspension and a uniform slurry was formed by sufficient stirring.
[0031] Completely immerse the glass fiber paper disc in the MOF slurry, hold for 1 minute, pull out, immerse again, and repeat 3 times to ensure that the fiber is fully impregnated. Then use a blower to remove excess slurry on the fiber surface to prevent the coating from being too thick or uneven. Subsequently, the treated glass fiber paper is placed in a 120°C oven for heat drying to promote the volatilization of the solvent in the slurry and the curing of the material. After drying, take out the glass fiber paper and let it cool naturally to room temperature. Then immerse the glass fiber paper in a 0.1g / mL curing agent calcium chloride solution for 10 minutes. Finally, the treated glass fiber paper is placed in a 120°C oven for heat drying to obtain a composite material.
[0032] Performance test: The coating rate (adhesion rate) of MOFs materials was measured by weighing comparison; the prepared porous composite material was weighed after being blown by wind at 50 m / s for 24 hours, and the adhesion layer shedding rate (24-hour powder loss rate) was calculated by the mass of the porous composite material before and after blowing. The test results are shown in Table 2.
[0033] Table 2
[0034] Experimental Example 3 The effects of adding different curing agents and not adding curing agents on the properties of porous composite materials based on MOFs materials are studied. The specific operations are as follows: A certain amount of UiO-66 MOFs material was weighed and evenly dispersed in water to form a uniform suspension with a concentration of 0.5 g / mL. Subsequently, a binder, sodium alginate, was added to the suspension and stirred to form a uniform slurry, with the binder accounting for 5% of the mass of the MOFs material.
[0035] Completely immerse the glass fiber paper disk in the MOF slurry for 1 minute, pull it out, immerse it again, and repeat 3 times to ensure that the fibers are fully wetted. Subsequently, use a blower to remove the excess slurry on the fiber surface to prevent the coating from being too thick or uneven. Then, place the treated glass fiber paper in an oven at 120 °C for thermal drying to promote the volatilization of the solvent in the slurry and the curing of the material. After drying, take out the glass fiber paper and let it cool naturally to room temperature.
[0036] Immerse the glass fiber paper in solutions of different curing agents (sodium chloride, calcium chloride, calcium sulfate, zinc chloride, zinc nitrate, magnesium chloride, barium chloride, iron chloride) for treatment, and also treat it without using a curing agent. When the concentration of the curing agent is 0.1 g / mL, immerse it for 10 minutes. Place the treated glass fiber paper in an oven at 120 °C for thermal drying to obtain the composite material.
[0037] Performance test: Measure the coating rate (adhesion rate) of the MOFs material by weighing and comparing. The calculation formula is: (M 1 -M 0 ) / M 0 ×100%, where M 1 is the total mass after coating; M 0 is the initial mass of the carrier.
[0038] Weigh the prepared porous composite material after blowing it with a wind speed of 50 m / s for 24 hours. Calculate the shedding rate of the adhesion layer (powder shedding rate in 24 hours) based on the mass of the porous composite material before and after blowing.
[0039] The powder shedding rate calculation formula is: M 2 -M 1 / (M 1 -M 0 )×100%, where M 2 is the mass after blowing; M 1 is the mass before blowing; M 0 is the initial mass of the carrier.
[0040] The test results are shown in Table 3.
[0041] Table 3
[0042] Example 1 A preparation method of a porous composite material based on MOFs material, comprising the following steps: Weigh a certain amount of UiO-66 MOFs material, and uniformly disperse it in water to form a uniform suspension with a concentration of 0.5 g / mL. Subsequently, add sodium alginate as a binder to this suspension, and form a uniform slurry through sufficient stirring. The binder accounts for 5% of the mass of the MOFs material.
[0043] Completely immerse the glass fiber paper disc in the MOF slurry, hold for 1 minute, pull out, immerse again, and repeat 3 times to ensure that the fiber is fully impregnated. Then use a blower to remove excess slurry on the fiber surface to prevent the coating from being too thick or uneven. Subsequently, the treated glass fiber paper is placed in a 120°C oven for heat drying to promote the volatilization of the solvent in the slurry and the curing of the material. After drying, take out the glass fiber paper and let it cool naturally to room temperature. Then immerse the glass fiber paper in a calcium chloride solution with a concentration of 0.1g / mL for 10 minutes. Finally, the treated glass fiber paper is placed in a 120°C oven for heat drying to obtain a porous composite material.
[0044] Performance test: The coating rate (adhesion rate) of MOFs materials was measured by weighing comparison. The prepared porous composite material was blown at a wind speed of 50 m / s for 24 hours and then weighed. The adhesion layer shedding rate (24-hour powder loss rate) was calculated based on the mass of the porous composite material before and after blowing.
[0045] Example 2 A method for preparing a porous composite material based on MOFs material comprises the following steps: A certain amount of MIL-101 or its derivatives are weighed and dispersed in water to form a uniform suspension with a concentration of 0.2 g / mL. Subsequently, a binder, sodium alginate, is added to the suspension and a uniform slurry is formed by sufficient stirring. The binder accounts for 5% of the weight of the MOFs material.
[0046] Completely immerse the glass fiber disc in the MOF slurry, hold for 1 minute, pull out, immerse again, and repeat 3 times to ensure that the fiber is fully impregnated. Then use a blower to remove excess slurry on the surface of the glass fiber disc to prevent the coating from being too thick or uneven. Subsequently, the treated glass fiber disc paper is placed in an oven at 120°C for heat drying to promote the volatilization of the solvent in the slurry and the curing of the material. After drying, take out the fiber disc and let it cool naturally to room temperature. Then immerse the glass fiber disc in a 0.1g / ml calcium chloride solution for 10 minutes. Finally, place the treated fiber disc in an oven at 120°C for heat drying to obtain a porous composite material.
[0047] Performance test: The coating rate (adhesion rate) of MOFs materials was measured by weighing comparison. The prepared porous composite material was blown at a wind speed of 50 m / s for 24 hours and then weighed. The adhesion layer shedding rate (24-hour powder loss rate) was calculated based on the mass of the porous composite material before and after blowing.
[0048] Example 3 A method for preparing a porous composite material based on MOFs material comprises the following steps: Weigh a certain amount of MOF-801 series MOFs materials with an analytical balance, disperse them in water to form a homogeneous suspension with a concentration of 0.5 g / mL. Subsequently, add sodium alginate as a binder to the suspension, and form a homogeneous slurry through sufficient stirring. The binder accounts for 5% of the mass of the MOFs materials.
[0049] Completely immerse the glass fiber paper in the MOF slurry for 2 minutes, pull it out, immerse it again, and repeat 3 times to ensure that the fibers are fully wetted. Then use a blower to remove the excess slurry on the fiber surface to prevent the coating from being too thick or uneven. Subsequently, place the treated glass fiber paper in an oven at 120 °C for thermal drying to promote the volatilization of the solvent in the slurry and the curing of the material. After drying, take out the glass fiber paper and let it cool naturally to room temperature. Then immerse the glass fiber paper in a 0.1 g / mL barium chloride solution as a curing agent for 10 minutes. Finally, place the treated glass fiber paper in an oven at 120 °C for thermal drying to obtain a porous composite material.
[0050] Performance test: Measure the coating rate (adhesion rate) of the MOFs materials by weighing and comparison; weigh the prepared porous composite material after blowing it with a wind speed of 50 m / s for 24 hours, and calculate the adhesion layer shedding rate (powder shedding rate in 24 hours) based on the mass of the porous composite material before and after blowing.
[0051] Example 4 A preparation method of a porous composite material based on MOFs materials, comprising the following steps: Weigh a certain amount of MIL-100, disperse it in water to form a homogeneous suspension with a concentration of 0.3 g / mL. Subsequently, add sodium alginate as a binder to the suspension, and form a homogeneous slurry through sufficient stirring. The binder accounts for 5% of the mass of the MOFs materials.
[0052] Completely immerse the sponge in the MOF slurry for 3 minutes, pull it out, immerse it again, and repeat 3 times to ensure that the sponge is fully wetted. Then use a blower to remove the excess slurry on the sponge to prevent the coating from being too thick or uneven. Subsequently, place the treated sponge in an oven at 120 °C for thermal drying to promote the volatilization of the solvent in the slurry and the curing of the material. After drying, take out the sponge and let it cool naturally to room temperature. Then immerse the sponge in a 0.1 g / mL calcium chloride solution for 20 minutes. Finally, place the treated sponge in an oven at 120 °C for thermal drying to obtain a porous composite material.
[0053] Performance test: Measure the coating rate (adhesion rate) of the MOFs materials by weighing and comparison; weigh the prepared porous composite material after blowing it with a wind speed of 50 m / s for 24 hours, and calculate the adhesion layer shedding rate (powder shedding rate in 24 hours) based on the mass of the porous composite material before and after blowing.
[0054] Example 5 A method for preparing a porous composite material based on MOFs materials, comprising the following steps: Weigh a certain amount of MOF-808 or its derivatives using a platform scale and disperse them in water to form a uniform suspension with a concentration of 0.5 g / mL. Subsequently, add the binder sodium alginate to the suspension and form a uniform slurry through sufficient stirring. The binder accounts for 5% of the mass of the MOFs material.
[0055] Completely immerse the cleaned foam metal in the MOF slurry for 3 minutes, pull it out, immerse it again, and repeat this 3 times to ensure that the foam metal is fully wetted. Then use a blower to remove the excess slurry on the surface of the foam metal to prevent the coating from being too thick or uneven. Subsequently, place the treated foam metal in an oven at 120 °C for heat drying to promote the volatilization of the solvent in the slurry and the curing of the material. After drying, take out the foam metal and let it cool naturally to room temperature. Then immerse the foam metal in a 0.1 g / mL calcium chloride solution for 20 minutes. Finally, place the treated foam metal in an oven at 120 °C for heat drying to obtain the porous composite material.
[0056] Performance test: Measure the coating rate (adhesion rate) of the MOFs material by weighing and comparing; weigh the prepared porous composite material after blowing it with a wind speed of 50 m / s for 24 hours, and calculate the shedding rate of the adhesion layer (powder shedding rate in 24 hours) based on the mass of the porous composite material before and after blowing.
[0057] Example 6 A method for preparing a porous composite material based on MOFs materials, comprising the following steps: First, weigh a certain amount of MIL-160 or its derivatives using weighing equipment and disperse them in water to form a uniform suspension with a concentration of 1 g / mL. Subsequently, add the binder sodium alginate to the suspension and form a uniform slurry through sufficient stirring. The binder accounts for 5% of the mass of the MOFs material.
[0058] Completely immerse the non-woven fabric in the MOF slurry for 3 minutes, pull it out, immerse it again, and repeat this 3 times to ensure that the non-woven fabric is fully wetted. Then use a blower to remove the excess slurry on the non-woven fabric to prevent the coating from being too thick or uneven. Subsequently, place the treated non-woven fabric in an oven at 120 °C for heat curing to promote the volatilization of the solvent in the slurry and the curing of the material. After drying, take out the non-woven fabric and let it cool naturally to room temperature. Then immerse the non-woven fabric in a 0.1 g / mL calcium chloride solution for 10 minutes. Finally, place the treated non-woven fabric in an oven at 120 °C for heat drying to obtain the porous composite material.
[0059] Performance test: Measure the coating rate (adhesion rate) of MOF materials by weighing and comparing; weigh the prepared porous composite materials after purging with a wind speed of 50 m / s for 24 hours, and calculate the shedding rate of the adhesion layer (powder shedding rate in 24 hours) based on the mass of the porous composite materials before and after purging.
[0060] The test results of the porous composite materials prepared in Examples 1-6 are shown in Table 4.
[0061] Table 4
[0062] As can be seen from Table 4, the specific surface area of the adhesion layer of the porous composite materials prepared in the examples of the present invention is only slightly smaller than that of the MOF material powder. The adhesion rate of the adhesion layer of the porous composite materials prepared in the examples of the present invention is as high as 45%, and after testing, the powder shedding rate in 24 hours is less than 0.5%, as low as 0.1%.
[0063] Samples were taken from the porous composite materials prepared in Examples 1-6, and X-ray diffraction (XRD) was used to analyze the structure of their adhesion layers. Figures 1 - 6 is the X-ray diffraction pattern of the porous composite materials prepared in Examples 1-6. As Figures 1 - 6 can be seen, the adhesion layer of the porous composite materials prepared by the coating technology still has sharp diffraction peaks, proving that using this coating process to prepare porous composite materials can maintain the structural stability of MOF materials and will not cause the collapse of the framework structure of MOF materials.
[0064] Isothermal adsorption and desorption tests were carried out on the porous composite materials prepared in Examples 1-6, and the test conditions were nitrogen adsorption and desorption at 77K. Figures 7 - 12 is the nitrogen adsorption and desorption curve of the porous composite materials prepared in Examples 1-6. Based on the specific surface area data and the adsorption and desorption curve data in Table 4, it can be seen that compared with the MOF material powder, although the specific surface area of the porous composite materials prepared by the coating technology is only slightly smaller than that of the powder, the pore environment of the adhesion layer of the prepared MOF materials has not changed, maintaining the characteristics of high specific surface area and excellent adsorption performance of MOF materials. This provides a solid experimental basis for the industrial application of the porous composite materials based on MOF materials provided by the present invention in the field of high-performance adsorbents.
[0065] The above-described embodiments only represent several implementation manners of the present invention, and their descriptions are relatively specific and detailed, but they should not be construed as limiting the scope of the patent of the present invention. It should be noted that for those of ordinary skill in the art, without departing from the concept of the present invention, several modifications and improvements can still be made, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the appended claims.
Claims
1. A method for preparing a porous composite material based on MOFs material, characterized in that: The following steps are involved: Dispersing MOFs material to obtain MOF slurry; then adding a polyhydroxy polymer binder to obtain a mixed slurry; distributing the mixed slurry on the surface of a substrate material by dipping or spraying, and curing to obtain a primary porous composite material; then impregnating the primary porous composite material with a curing agent, and finally drying to obtain a porous composite material based on MOFs material; The curing agent is selected from at least one of calcium chloride, calcium sulfate, zinc chloride, magnesium chloride, zinc nitrate, and barium chloride; the polyhydroxy polymer binder is selected from at least one of sodium alginate, chitosan, and hyaluronic acid; The added amount of the polyhydroxy polymer binder is 1.0%-12.0% of the mass of the MOFs material.
2. The preparation method according to claim 1, characterized in that: The MOFs material includes at least one of MOF-801 series, MOF-808 series, MIL series, UiO-66 series, ZIF series, and PCN series MOFs materials.
3. The preparation method according to claim 2, characterized in that: The concentration of the MOF slurry is 0.1 g / mL-1.0 g / mL.
4. The preparation method according to claim 1, characterized in that: The added amount of the polyhydroxy polymer binder is 1.2%-10.0% of the mass of the MOFs material.
5. The preparation method according to any one of claims 1 to 4, characterized in that: The base material includes one of glass fiber paper, non-woven fabric, metal products, sponge, and silica gel products.
6. The preparation method according to claim 1, characterized in that: The curing agent is selected from at least one of calcium chloride, calcium sulfate, zinc chloride, zinc nitrate and barium chloride.
7. The preparation method according to claim 6, characterized in that: The curing agent is prepared into a curing agent solution and then impregnated into the primary porous composite material. The concentration of the curing agent solution is 0.05 g / mL-1.0 g / mL.
8. The preparation method according to claim 7, characterized in that: The concentration of the curing agent solution is 0.1 g / mL-0.5 g / mL.
9. A porous composite material based on MOFs material, characterized in that: Prepared by the preparation method described in any one of claims 1-8; the porous composite material comprises a base material and a MOFs material attached to the surface of the base material.
10. Use of the porous composite material based on MOFs material according to claim 9 in the preparation of porous adsorption materials.
Citation Information
Patent Citations
Molded metal-organic framework material and molding method thereof
CN107029670A
Preparation method, product and application of ultra-stable MOFs-based porous sponge
CN112295603A
Hydrogel type composite material, preparation method thereof, method for removing benzene series by using hydrogel type composite material and application of hydrogel type composite material
CN114100582A